2017
DOI: 10.1534/g3.117.041608
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of a Rice Nested Association Mapping Population

Abstract: Describing the genetic diversity in the gene pool of crops will provide breeders with novel resources for varietal improvement. Nested Association Mapping (NAM) populations are uniquely suited for characterizing parental diversity through the shuffling and fixation of parental haplotypes. Here, we describe a set of 1879 rice NAM lines created through the selfing and single-seed descent of F1 hybrids derived from elite IR64 indica crossed with 10 diverse tropical japonica lines. Genotyping data indicated tropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 86 publications
0
49
0
Order By: Relevance
“…Most of the studies reported the genetic maps between a range of 600–1500 loci in biparental populations, except a WGRS based genetic map with 8869 loci in 3120 cM (Agarwal et al , ). In other crops, similar studies using NAM populations successfully dissected the genetics of complex traits and facilitated candidate gene discovery, such as in soybean (Song et al , ; Xavier et al , ), maize (McMullen et al , ; Yu et al , ), wheat (Hu et al , ; Jordan et al , ) and rice (Fragoso et al , ). In most of these studies, the GWAS analysis was performed in NAM populations instead of constructing genetic maps.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies reported the genetic maps between a range of 600–1500 loci in biparental populations, except a WGRS based genetic map with 8869 loci in 3120 cM (Agarwal et al , ). In other crops, similar studies using NAM populations successfully dissected the genetics of complex traits and facilitated candidate gene discovery, such as in soybean (Song et al , ; Xavier et al , ), maize (McMullen et al , ; Yu et al , ), wheat (Hu et al , ; Jordan et al , ) and rice (Fragoso et al , ). In most of these studies, the GWAS analysis was performed in NAM populations instead of constructing genetic maps.…”
Section: Discussionmentioning
confidence: 99%
“…In maize, where this technique was developed, it was first used to map genes associated with flowering time (Buckler et al ., ; Figure ). Since then it has been extended for use in rice (Fragoso et al ., ), wheat (Bajgain et al ., ) and barley (Maurer et al ., ).…”
Section: Finding Associations Between Genotype and Phenotype: Linkagementioning
confidence: 99%
“…These secondary mapping populations are required to facilitate more comprehensive analysis of target QTLs (Yano, 2001). More recently in rice, multi-parent populations called multi-parent advanced generation intercross (MAGIC; Bandillo et al, 2013), CSSLs (Bessho-Uehara et al, 2017;Ogawa et al, 2016) and nested-association mapping populations (Fragoso et al, 2017) have been used for QTL mapping.…”
Section: Approaches To Qtl Mappingmentioning
confidence: 99%